Implementation of BMB3 in the Implementation of Guidance and Counseling Service Management in Educational Institutions - Torly Amora Jofipasi; Neviyarni S; Yarmis Sukur; Jon Efendi (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Based on Law no. 20/2003, article 1 paragraph (1), "education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, morals. noble, and skills needed by himself, the nation's community, and the state." BMB3 is something that needs to be considered in education in order to achieve the 6 educational focuses explained in the law. With BMB3, the process of implementing BK in management can be structured and have competent implementation because it is based on BMB3. This article also discusses the management of guidance and counseling services which assesses the implementation of management of guidance and counseling services in education today, how the application of BMB3 contributes to the implementation of management of guidance and counseling services in education today. The methods used include literature reviews along with critical analysis of research being conducted on the particular topic to be studied.